Exploring strategic perspectives on the Special Constabulary. (December 2022) - Callender, Matthew; Britton, Iain; Knight, Laura
This article explores senior and strategic perspectives on the volunteer Special Constabulary in England and Wales, based on 38 interviews with senior police leaders. The strategic context and leadership of Special Constabularies represents an overlooked element of police leadership, given the scale and potential of volunteer officers to impact upon policing delivery and reform. The paper identifies tension between a traditional strategic paradigm that frames bounded expectations of the role of Special Constables, emphasising differences between them and their paid counterparts, and considerations of police reform which prompt different thinking in respect of practice, identity and integration of volunteer officers.